Pelatihan Pengolahan Akuntansi Sederhana di UMKM Kripik Tempe XYZ Balikpapan Utara - Dian Saripujiana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This community service activity aims to improve basic accounting literacy for Micro, Small, and Medium Enterprises (MSMEs) through financial recording training and simple financial report making. Many MSME actors do not have a neat bookkeeping system, making it difficult to find out net income and access financing from financial institutions. Therefore, the introduction of simple accounting is a strategic step to encourage more professional and sustainable business management. This activity was carried out by a team of lecturers accompanied by students, with a participatory approach and based on direct practice. The training material includes basic understanding of accounting, recording daily transactions, preparing income statements, and simulating the use of financial statements for working capital submissions. Through this method, it is hoped that there will be an effective and applicable transfer of knowledge from academics to the public. The results of the activity showed that participants were able to understand the importance of financial recording and began to implement a simple bookkeeping system in their business operations. In addition, participants also showed increased confidence in compiling financial statements that can be used as supporting documents in applying for financing to cooperatives, banks, or other financial institutions. This activity not only provides practical benefits for MSME actors, but also strengthens the role of universities in community economic empowerment. In the future, similar activities can be developed with the integration of digital technology to support more efficient and accurate financial recording.